Alcott Farrar Elwell collection - Elwell, Alcott Farrar, 1886-1962.
Typewritten copy of a journal kept by Elwell while serving as camp cook for the U.S. Geodetic Survey's Roosevelt Lignite Conservation Study in Wyoming, 1908, with a map, photographs, and pages from a holograph notebook of recipes. Includes the October 1966 issue of Annals of Wyoming, containing excerpts from the journal.
In part, photocopies.
Cook.
Collection material in English.
Keywords: U.S. Coast and Geodetic Survey; Geological Survey (U.S.) -- Roosevelt Lignite Conservation Study; Conservation of natural resources -- Wyoming; Cooking; Wyoming -- Discovery and exploration; Cooks